The Role of Mobile Devices in the Era of Digital Learning in Elementary Schools - Arman Paramansyah; Rino Lengam; Awal Kurnia Putra Nasution (Journal of Social Science Utilizing Technology, 2024)
Background. The use of mobile devices has brought significant changes to learning in elementary schools, offering quick access to learning resources and increasing interactivity in the learning process. This reflects a paradigm shift in education towards the use of technology as an effective and dynamic learning tool. Purpose. The aim of this research is to fill the existing knowledge gap in the literature by investigating the views of PGSD students and elementary school teachers regarding the use of mobile devices in learning at school base. It is hoped that this research can provide a deeper understanding of the potential of mobile devices in supporting the learning process at the basic level, as well as becoming a basis for developing more effective learning strategies in the future. Method. This research methodology uses a quantitative approach through a survey model involving 30 respondents, consisting of PGSD students and elementary school teachers. Data collection was carried out through distributing online questionnaires using Google Form. Data analysis was carried out using a quantitative data analysis approach, paying attention to the validity of the data through comparison with other relevant data sources. Results. The results of the questionnaire analysis show that the majority of students use mobile devices regularly, indicating widespread adoption of technology in the educational context. However, challenges that need to be overcome include a lack of training and support for educators, as well as school policies that may not fully support the integration of technology in the curriculum.   Conclusion. The integration of mobile devices in learning in elementary schools promises many benefits, but also faces challenges that need to be overcome. With adequate support, it is hoped that the use of mobile devices can become an effective and inclusive learning tool for all students, preparing them to face the demands of an increasingly digitally connected world.